Environmental Impact of Synthetic Dyes on Groundwater in Malaysia: Sources, Distribution, Transport Mechanisms, and Mitigation Strategies - Chan, Alfred; Rubiyatno; Akhmetov, Zarina (Tecno Scientifica Publishing, 2024)
Synthetic dyes, extracted from natural sources like insects, plants, coal, and ochre, have become prevalent due to their advantages over natural dyes. However, their production has led to increased environmental pollution, particularly in groundwater. Groundwater contamination from synthetic dyes occurs through advection, dispersion, and retardation. This review aims to highlight the environmental impacts of synthetic dyes on groundwater, elucidate the mechanisms of dye transport, and propose effective strategies for monitoring and mitigating contamination. Urban runoff carries dyes from surfaces such as roofs, parking lots, and roads into stormwater systems, while agricultural runoff transports dyes from products like soil conditioners, fertilizers, and seed coatings into water bodies. In groundwater, dyes move through the aquifer via advection, dispersion, and retardation, all influenced by groundwater flow and geological conditions. The advection process involves the bulk movement of groundwater carrying dissolved dyes, while dispersion causes dyes to spread and dilute over time and distance. Retardation, which involves the adsorption of dye molecules onto soil particles, slows dye movement, prolonging their presence in groundwater. Understanding the sources, distribution, and movement of synthetic dyes in groundwater is crucial for developing strategies to protect water resources and reduce environmental and health impacts. The extensive use of dyes in industrial and domestic activities necessitates comprehensive monitoring and management to ensure sustainable groundwater quality.